Corporate warriors the rise of the privatized military industry - Singer, P. W. (Peter Warren) (Cornell studies in security affairs, 2004)
In this book, Singer provides the first account of the military services industry and its broader implications. The privitization of warfare allows startling new capbilities and efficiencies in the ways that war is carried out. At the same time, however, Singer finds that the entrance of the profit motive onto the battlefield raises a series of troubling questions--for democracy, for ethics, for management, for human rights, and for national security